Proceedings of Offshore Technology Conference 2009
DOI: 10.4043/otc-20129-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Horizontal Well Performance in Nonuniform Pressure Environments Using Passive Inflow Control Devices

Abstract: Passive Inflow Control Devices (ICDs) are used to enhance performance of horizontal wells in unfavorable environments, such as nonuniform permeability and/or pressure along horizontal sections. This is the first attempt at using ICDs to manage inflow along horizontal wells with substantial reservoir pressure differential. This paper presents how passive ICD completion technology is used to optimize well productivity and reduce water production in a well with significant reservoir pressure differential across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In addition, it is observed that installing ICDs do not guarantee a uniform flow in horizontal wells. A well-designed ICD completion, assisted by wellbore hydraulic modeling, however, can promote production from the entire horizontal lateral and mitigate the effect of the severe pressure gradients, eliminating cross-flows (Krinis et al 2009). …”
Section: Inflow Profile Typesmentioning
confidence: 99%
“…In addition, it is observed that installing ICDs do not guarantee a uniform flow in horizontal wells. A well-designed ICD completion, assisted by wellbore hydraulic modeling, however, can promote production from the entire horizontal lateral and mitigate the effect of the severe pressure gradients, eliminating cross-flows (Krinis et al 2009). …”
Section: Inflow Profile Typesmentioning
confidence: 99%
“…The most prolific zones with matrix permeability ranging between 300 mD and 2,000 mD are located at the top of reservoir (Krinis, D. et al 2009). The field has a production history of more than 50 years.…”
Section: Introductionmentioning
confidence: 99%